Pendekatan Kaunseling dalam Dakwah Bagi Kesejahteraan Insan dan Peradaban Ummah - Tengku Kasim, Tengku Sarina Aini; Che Husain, Faridah (Jurnal Usuluddin, 2006)
Islamic counseling is not only an approach to assist in resolving crisis, but it is also regarded as a social service to guide people in all aspects of human life. The guidance is set up based upon the rules that have been determined by Islam in the Holy Quran and al-Sunnah. In counseling, every individual will be assisted and guided to make decision base on rasional and faith. Counseling can be considered as a technique in da wah because amongst the role of a counselor is congruent to the role of pendakwah i.e. to encourage people toward rasional thinking before making any decision or taking any action. Both counseling and dawah stress on the importance of guiding a person towards any transformation concerning his behaviour and way of thinking in everyday life. Hence, this paper will deliberate the importance of counseling approach in dawah to achieve individual harmonious and ummah civilization. An ideal counseling approach in dawah will result in the development of individual self-esteem which will provide huge impact towards ummah civilization.